Analysis of the composition of culturable airborne microorganisms in the archaeological excavation protection site of the Nanhai No. 1 Ancient Shipwreck - Ma, Kaixuan; Wang, Yu; Yang, Xinyu; Wang, Cen; Han, Yeqing; Huang, Xinduo; Guo, Peifeng; Du, Jing; Chen, Yue; Pan, Jiao (Frontiers in Microbiology, 2022)
After the recovery of the ship from the sea on 2007, the Nanhai No. 1 Ancient Shipwreck is currently exposed to the air. Air microorganisms settle on wooden shipwrecks, and they can use wood matrix to grow and multiply, causing biocorrosion and biodegradation. In this study, a systematical survey of the composition of culturable airborne microorganisms was performed at the conservation site of the Nanhai No. 1 Ancient Shipwreck. Airborne microorganisms were collected from seven sites in the preservation Nanhai No. 1 area over five periods. Molecular identification of the culturable microorganisms isolated from the air was done by sequencing both 16S rRNA (bacteria) and ITS (fungi) gene regions. The biodegradability of these strains was evaluated by degradation experiments with cellulose and lignin as substrate. The results showed that the composition of the isolated microbial communities was different in each period, and microbial spatial distribution was dissimilar in the same period. In the recent 2020, the dominant bacterial genus was Acinetobacter, and the dominant fungal genera were Penicillium, Aspergillus, and Cerrena. Acinetobacter spp. can degrade cellulose and lignin. Penicillium spp., Aspergillus spp., and Cerrena spp. degraded cellulose but only Cerrena spp. could utilize lignin. These dominant strains may have a harmful effect on the Nanhai No. 1 Ancient Shipwreck. This study provides data on the airborne microbial community found inside the protective chamber where Nanhai No. 1 Shipereck is placed, which can be used as a reference basis for the future conservation of the ship.